EDUCATIONAL STANDARD IN PAKISTAN: WHETHER FALLING OR RISING? - Farzana Mallah1 , Abdul Nabi Gorchani2 , Farheen Shaikh3, Tazeen Shah4 , Shafaq Ansari5 Hanna Khair Tunio6 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT INTRODUCTION: Pakistan has Islamic country assorted in huge socially and phonetically through South Asia nations and in South of Arabian Sea with lined of Afghanistan, Iran, China and India in larger parts of Muslim apportioned from India in 1947. Financial inconsistencies exist in Pakistan is essential to comprehend through country and metropolitan regions which comprises of four territories incongruities in enormous effect on instructive results, remembering tremendous holes for admittance to schooling and in general instructive accomplishment. After the situation of COVID-19, the academic all over the globe has been affected very seriously, some departments were tried to maintain and complete the syllabus online, but there were some departments which were purely approached thru physical presence. In parallel to other departments health professional education was affected very seriously. The practical were affected highly at unavoidable levels. This will lead a harmful effect on the professional education, besides the world Pakistan was also affected very seriously during this period, Pakistan’s not only economy nut also health and education dropped as sky fall. Here in this mini review we had tried to do overall assessment that whether educational standard here has been affected or not, or the nation has maintained the standards of education.